2014
DOI: 10.1007/s00586-014-3416-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transplantation of olfactory ensheathing cells in chronic spinal cord injury: a systematic review and meta-analysis

Abstract: Given the results from our study, we conclude that OEC transplantation appears to be safe, although the evidence for efficacy is modest and requires the support of prospective, randomized trials in larger cohorts of patients. Further randomized controlled trials utilizing strict therapy programs and implanted cell selections are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 48 publications
0
52
0
Order By: Relevance
“…202 Subsequently studies transplanted mucosal tissue, as opposed to 42 purified OECs, with conflicting results 203 204 Other trials have investigated other transplanted cells, including OECs and olfactory nerve fibroblasts, Schwann cells and a combination of OECs and Schwann cells 205,206 . A systematic review of the use of OECs in SCI echoed the positive findings found in other trials 207 . More recently, data from a phase 1 trial reported motor and sensory improvements and no serious adverse events 1 year post transplantation of autologous mucosal OECs and olfactory nerve fibroblasts into the spinal cords of patients with AIS impairment grade A injuries (n=6) 205 .…”
Section: [H2] Current Clinical Studiesmentioning
confidence: 72%
“…202 Subsequently studies transplanted mucosal tissue, as opposed to 42 purified OECs, with conflicting results 203 204 Other trials have investigated other transplanted cells, including OECs and olfactory nerve fibroblasts, Schwann cells and a combination of OECs and Schwann cells 205,206 . A systematic review of the use of OECs in SCI echoed the positive findings found in other trials 207 . More recently, data from a phase 1 trial reported motor and sensory improvements and no serious adverse events 1 year post transplantation of autologous mucosal OECs and olfactory nerve fibroblasts into the spinal cords of patients with AIS impairment grade A injuries (n=6) 205 .…”
Section: [H2] Current Clinical Studiesmentioning
confidence: 72%
“…At least 10 studies of patients with chronic SCI treated with OECs have been described (cumulative n = 1,193). A recent meta‐analysis found no significant increase in adverse events after OEC transplant; however, higher‐quality studies are still required to define efficacy [102].…”
Section: Cell‐based Approachesmentioning
confidence: 99%
“…Partial functions and the quality of life have been improved following transplantation of cells into cord parenchyma, intrathecal administration of cells (lesion area or lumbar subarachnoid space), intravascular infusion of cells, and by multiple routes of administration. 11,[58][59][60][61][62][63][64][65][66][67][68] Increasing studies have showed that extracellular vesicles such as exosomes have recently been suggested to mediate neurorestorative effects, [69][70][71] and may offer a possible alternative therapeutic strategy for SCI in future.…”
Section: Cell Therapymentioning
confidence: 99%